2011
DOI: 10.1186/1752-0509-5-199
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory coordination of clustered microRNAs based on microRNA-transcription factor regulatory network

Abstract: BackgroundMicroRNA (miRNA) is a class of small RNAs of ~22nt which play essential roles in many crucial biological processes and numerous human diseases at post-transcriptional level of gene expression. It has been revealed that miRNA genes tend to be clustered, and the miRNAs organized into one cluster are usually transcribed coordinately. This implies a coordinated regulation mode exerted by clustered miRNAs. However, how the clustered miRNAs coordinate their regulations on large scale gene expression is sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 42 publications
(44 reference statements)
3
54
0
1
Order By: Relevance
“…Many studies have indicated that the acquisition of an aggressive cancer phenotype through EMT, as well as other cellular events, may be understood by evaluating the regulatory interaction between transcription factors and miRNAs [32,33]. However, direct evidence of these interactions in EMT is still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have indicated that the acquisition of an aggressive cancer phenotype through EMT, as well as other cellular events, may be understood by evaluating the regulatory interaction between transcription factors and miRNAs [32,33]. However, direct evidence of these interactions in EMT is still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, TFs other than STAT1, have been classified into two types: homo-clusters (composed of miRNAs from a single family) and hetero-clusters (miRNAs from multiple families). 46 Usually members of the same miRNA family target a similar set of mRNAs because they share the same seed region, 47 which predominantly determines the targets of miRNAs. 48 Accordingly, we have identified a co-regulated homocluster (miR-29a~29b1*, data not shown) and two hetero-clusters (miR-23a~27a and miR-23b~27b), which had reverse expression patterns: miR-23a~27a was upregulated, while miR-23b~27b was downregulated (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…same versus various families, respectively), suggesting distinct roles in biological processes (Wang et al, 2011). As for other transcribed RNAs, miRNA expression is itself regulated by epigenetic factors such as DNA methylation and chromatin structure (Iorio et al, 2010).…”
Section: Histone Modificationsmentioning
confidence: 99%